influência da densidade de estocagem no desempenho produtivo do acará-bandeira (Pterophyllum scalare) - Nagata, Mariana Midori [UNESP]; Takahashi, Leonardo Susumu [UNESP]; Gimbo, Rodrigo Yukihiro [UNESP]; Kojima, Juliana Tomomi [UNESP]; Biller, Jaqueline Dalbello [UNESP] (My University, 2010)
The present study aimed to evaluate the effects of three different stock densities (0.33; 0.67 e 1.00 fish L-1) on freshwater angelfish productive performance reared in aquarium. Fish were fed with commercial diets during 35 days in two diary meals. The experimental design was entirely randomized and for each density were used four replicates. Were evaluated physical-chemical water parameters: temperature, oxygen dissolved concentration and total ammonia concentration and growth performance parameters: weight gain, feed conversion, specific growth rate, final standard length, conduction factor and length uniformity. Results were submitted to variance analysis and means were compared by Tukey's test (α = 0.05), it was used the statistic program ESTAT 2.0. Mortality was not observed in any tested density. On physical-chemical water parameters, total ammonia level increased significantly with stock density increasing, but they did not showed clinical signs of ammonia toxicity. As there were no significant differences between treatments, stock density 1.00 fish L-1 is the most indicated because it allows higher production.
Influence of stock density in productive performance of freshwater angelfish (Pterophyllum scalare)
Keywords: Management; Production; Pterophyllum scalare